Bending-resistant long-life flexible fibrous aqueous zinc-iodine battery and preparation method thereof
By in-situ crosslinking on fiber electrodes, the problem of separation between electrodes and electrolyte interfaces and corrosion of zinc negative electrodes in the bending and charging and discharge process of fibrous aqueous zinc-iodine batteries is solved, and the long cycle life and bending resistance are improved.
Patent Information
- Application Number
- CN202411687122.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing fibrous aqueous zinc-iodine batteries are separated from the boundary between the fiber electrode and the gel electrolyte during bending and charging and discharge, and the zinc negative electrode is corroded, resulting in a short cycle life.
Hydrogel electrolytes with high mechanical strength and high ionic conductivity are prepared by in-situ crosslinking on the fiber electrodes, and a stable interface between the fiber electrodes and the gel electrolyte is constructed to adapt to the deformation of the fiber electrodes during bending and charging and discharge, ensuring good contact between the electrode and the electrolyte.
The excellent cycle stability and bending resistance of flexible fibrous aqueous zinc-iodine batteries are achieved. The capacity retention rate reaches 91% after charging and discharging 3500 times at a 5C current density, and the initial capacity can still be maintained after 3000 times.
Smart Images

Figure CN119601791A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flexible aqueous secondary batteries, and in particular relates to a bending-resistant, long-life flexible fibrous aqueous zinc-iodine battery and a preparation method thereof. Background Art
[0002] The booming development of smart wearable devices has created a huge demand for highly flexible and safe energy supply devices. High-performance, high-safety and high-flexibility energy storage devices have broad application prospects in the fields of smart wearable devices. Fibrous flexible aqueous zinc-ion batteries have the advantages of low cost, light weight, small size, high safety and good weavability, and have made many progresses in recent years. However, the complex synthesis process and relatively low specific capacity of positive electrode materials such as manganese oxide, vanadium oxide, and Prussian blue analogs hinder the widespread application of fibrous flexible aqueous zinc ions.
[0003] In recent years, based on I - and I 2 The zinc-iodine battery, which can reversibly switch between I and Zn, stands out mainly due to its relatively high specific capacity (based on I 2 The mass is 211 mAh g -1 ), medium discharge potential (≈1.29V vs.Zn / Zn 2+ ), good redox reversibility and abundant marine reserves. Despite this, the preparation of fibrous aqueous zinc-iodine batteries with long cycle life still encounters significant challenges. The metal zinc negative electrode suffers from corrosion problems caused by zinc dendrites and iodide, which aggravates battery degradation. In addition, the interfacial separation between the fibrous electrode and the electrolyte caused by the bending process increases the internal resistance of the battery and causes the active material to fall off, limiting the cycle life of the battery. Therefore, it is urgent to develop a fibrous aqueous zinc-iodine battery with excellent cycle stability and flexibility. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a flexible fibrous aqueous zinc-iodine battery that is resistant to bending and has a long life, and a preparation method thereof. A hydrogel electrolyte with high mechanical strength and high ionic conductivity is prepared by in-situ crosslinking on the fiber electrode, and a stable interface between the fiber electrode and the gel electrolyte is constructed to adapt to the deformation of the fiber electrode during bending and charging and discharging, thereby ensuring good contact between the fiber electrode and the electrolyte, and effectively reducing the side reactions of the fiber zinc negative electrode. The flexible fibrous aqueous zinc-iodine battery of the present invention has the advantages of low cost, high specific capacity, and long cycle life, and has excellent bending resistance.
[0005] The above technical objectives of the present invention are achieved through the following technical solutions:
[0006] The present invention provides a bending-resistant, long-life flexible fibrous aqueous zinc-iodine battery, comprising the following components: a flexible fiber zinc negative electrode, a hydrogel electrolyte and a flexible fiber positive electrode, wherein the flexible fiber negative electrode is one of zinc wire, galvanized stainless steel wire and carbon fiber with electroplated zinc, the hydrogel electrolyte is a double-network hydrogel composed of sodium alginate and polyacrylamide, and the flexible fiber negative electrode is a carbon fiber coated with iodine-containing activated carbon slurry.
[0007] The present invention provides a method for preparing a flexible fibrous aqueous zinc-iodine battery that is resistant to bending and has a long life, comprising the following steps:
[0008] Step 1: immerse the flexible fiber zinc negative electrode in an aqueous solution of sodium alginate and polyacrylamide to coat a layer of pre-gel solution, and then immerse the fiber zinc negative electrode in a zinc salt aqueous solution to form a layer of gel electrolyte on the surface;
[0009] Step 2: Mix iodine-loaded activated carbon, conductive carbon black, polytetrafluoroethylene binder, and sodium carboxymethyl cellulose, add deionized water and stir to form a uniform slurry, apply the slurry on carbon fiber by dipping, and obtain an iodine-containing carbon fiber positive electrode after drying;
[0010] Step 3: The flexible fiber zinc negative electrode coated with gel electrolyte is twisted with the iodine-loaded iodine-containing carbon fiber positive electrode, and then coated with a layer of pre-gel solution of sodium alginate and polyacrylamide, and immersed in a zinc salt aqueous solution to form a layer of gel electrolyte to wrap the electrode, thereby obtaining a fiber-shaped zinc-iodine battery cell;
[0011] Step 4: The battery cell prepared in the previous step is coated with silicone rubber to encapsulate a flexible fibrous zinc-iodine battery.
[0012] The present invention is further configured as follows: the mass fraction of sodium alginate in the pre-gel solution of the hydrogel electrolyte is 2% to 5%, and the mass fraction of polyacrylamide is 0.5% to 5%.
[0013] The present invention is further configured as follows: the zinc salt is a mixture of one or more of zinc sulfate, zinc trifluoromethanesulfonate, zinc chloride, and zinc acetate, and the zinc salt concentration is 0.5 to 3.0 mol·L -1 The soaking time is 5min~6h.
[0014] The present invention is further configured as follows: the iodine loading on the iodine-containing carbon fiber positive electrode is 0.2 to 0.8 mg cm -1 .
[0015] Compared with the prior art, the present invention has the following beneficial technical effects:
[0016] The present invention uses a simple zinc salt solution soaking method to prepare a hydrogel electrolyte with high mechanical strength and high ionic conductivity by in-situ crosslinking on a fiber electrode. The hydrogel prepared by crosslinking sodium alginate and zinc ions has high mechanical strength. The addition of polyacrylamide further improves the ionic conductivity of the hydrogel and the stability of the zinc negative electrode and electrolyte interface, effectively solving the problem of separation of the fiber electrode and the gel electrolyte interface and corrosion of the zinc negative electrode during bending and charging and discharging of the flexible fiber-shaped zinc-iodine battery. The flexible fiber-shaped aqueous zinc-iodine battery prepared by the present invention has excellent cycle stability and bending resistance, reaching a current density of 5C (1C = 211mA·g -1 ) after 3500 charge and discharge cycles, the capacity retention rate is 91%, and after being bent 3000 times at a bending radius of 12mm and a bending angle of 90°, it can still maintain 80% of the initial capacity.
[0017] The preparation method of the flexible fibrous aqueous zinc-iodine battery provided by the present invention has the advantages of simple operation, low cost, high safety, continuous large-scale preparation, etc., and has good development and application prospects in the field of smart wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic diagram of the preparation process of a flexible aqueous zinc-iodine battery, from which the preparation process and structural composition of the fibrous zinc-iodine battery of the present invention can be seen.
[0019] Figure 2 The mechanical property test results of the hydrogel electrolytes containing sodium alginate (SA) and polyacrylamide (PAM) in different proportions prepared in Examples 1-5 show that the prepared hydrogels have good mechanical strength, and the mechanical strength of the prepared hydrogels decreases as the addition proportion of polyacrylamide increases.
[0020] Figure 3 The conductivity test results of the hydrogel electrolytes containing different ratios of sodium alginate (SA) and polyacrylamide (PAM) prepared in Examples 1-5 show that the hydrogel electrolyte prepared with a mass ratio of sodium alginate and polyacrylamide of 4:3 has the highest ionic conductivity (12.3 mS·cm- 1 ), while maintaining high mechanical strength.
[0021] Figure 4 The cycling performance of the zinc-zinc symmetric battery assembled using zinc wire and the hydrogel electrolyte prepared in Example 3 shows that at a current density of 2 mA cm -2 、Capacity 6.7mAh·cm -2 Under the condition of (zinc utilization 15%), the assembled Zn||Zn symmetric battery can be stably cycled for 450 hours, demonstrating its excellent long-cycle stability.
[0022] Figure 5 The charge and discharge curves of the flexible aqueous zinc-iodine battery prepared in Example 6 of the present invention at different rates are shown in Figure 1. -1 ) has 176mAh·g -1 Discharge capacity: at 10C rate, the discharge capacity is still 136mAh·g.
[0023] Figure 6 The cycle performance test results of the flexible aqueous zinc-iodine battery prepared in Example 6 of the present invention show that the capacity retention rate is 91% after 3500 charge and discharge cycles in the normal state at a rate of 5C, and the capacity retention rate is 80% after 2500 cycles in the bent state, proving that it has a long cycle life.
[0024] Figure 7 The capacity retention rate of the flexible aqueous zinc-iodine battery prepared in Example 6 of the present invention after being bent for different times at a bending radius of 12 mm and a bending angle of 90° is that it can still maintain 80% of the initial capacity after being bent 3000 times, proving that it has excellent flexibility. DETAILED DESCRIPTION
[0025] The following is a detailed description of the embodiments of the present invention. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, modifications or equivalent substitutions made to the present invention should all be included in the scope of the claims of the present invention.
[0026] In addition, in order to better illustrate the present invention, numerous specific details are given in the following specific embodiments. It will be understood by those skilled in the art that the present invention can also be implemented without these specific details.
[0027] The present invention will now be further described with reference to the embodiments and the accompanying drawings:
[0028] The present invention provides a method for preparing a flexible fibrous aqueous zinc-iodine battery that is resistant to bending and has a long life, comprising the following steps:
[0029] Step 1: immerse the flexible fiber zinc negative electrode in an aqueous solution of sodium alginate and polyacrylamide to coat a layer of pre-gel solution, and then immerse the fiber zinc negative electrode in a zinc salt aqueous solution to form a layer of gel electrolyte on the surface;
[0030] Step 2: Mix iodine-loaded activated carbon, conductive carbon black, polytetrafluoroethylene binder, and sodium carboxymethyl cellulose, add deionized water and stir to form a uniform slurry, apply the slurry on carbon fiber by dipping, and obtain an iodine-containing carbon fiber positive electrode after drying;
[0031] Step 3: The flexible fiber zinc negative electrode coated with gel electrolyte is twisted with the iodine-loaded iodine-containing carbon fiber positive electrode, and then coated with a layer of pre-gel solution of sodium alginate and polyacrylamide, and immersed in a zinc salt aqueous solution to form a layer of gel electrolyte to wrap the electrode, thereby obtaining a fiber-shaped zinc-iodine battery cell;
[0032] Step 4: The battery cell prepared in the previous step is coated with silicone rubber to encapsulate a flexible fibrous zinc-iodine battery.
[0033] The present invention is further configured as follows: the mass fraction of sodium alginate in the pre-gel solution of the hydrogel electrolyte is 2% to 5%, and the mass fraction of polyacrylamide is 0.5% to 5%.
[0034] The present invention is further configured as follows: the zinc salt is a mixture of one or more of zinc sulfate, zinc trifluoromethanesulfonate, zinc chloride, and zinc acetate, and the zinc salt concentration is 0.5 to 3.0 mol·L -1 The soaking time is 5min~6h.
[0035] The present invention is further configured as follows: the iodine loading on the iodine-containing carbon fiber positive electrode is 0.2 to 0.8 mg cm -1 .
[0036] Embodiment 1:
[0037] A method for preparing a hydrogel electrolyte for a flexible fibrous aqueous zinc-iodine battery, the specific preparation steps are as follows:
[0038] (1) Preparation of pre-gel solution
[0039] 4% by mass of sodium alginate and 1% by mass of polyacrylamide were added into deionized water, and the mixture was stirred and dissolved to obtain a transparent solution.
[0040] (2) Preparation of hydrogel electrolyte
[0041] The pre-gel solution prepared in the previous step was poured into a polytetrafluoroethylene mold and heated to a concentration of 0.5 mol·L -1 ZnSO 4 Soak in aqueous solution for 20 minutes to cross-link sodium alginate and zinc ions to obtain a hydrogel electrolyte.
[0042] Embodiment 2:
[0043] A method for preparing a hydrogel electrolyte for a flexible fibrous aqueous zinc-iodine battery, wherein the specific preparation steps are the same as those in Example 1, except that the mass fraction of sodium alginate contained in the prepared pregel solution is 4%, and the mass fraction of polyacrylamide is 2%.
[0044] Embodiment 3:
[0045] A method for preparing a hydrogel electrolyte for a flexible fibrous aqueous zinc-iodine battery, wherein the specific preparation steps are the same as those in Example 1, except that the mass fraction of sodium alginate contained in the prepared pregel solution is 4%, and the mass fraction of polyacrylamide is 3%.
[0046] Embodiment 4:
[0047] A method for preparing a hydrogel electrolyte for a flexible fibrous aqueous zinc-iodine battery, wherein the specific preparation steps are the same as those in Example 1, except that the mass fraction of sodium alginate and the mass fraction of polyacrylamide contained in the prepared pregel solution are 4% and 4%, respectively.
[0048] Embodiment 5:
[0049] A method for preparing a hydrogel electrolyte for a flexible fibrous aqueous zinc-iodine battery, wherein the specific preparation steps are the same as those in Example 1, except that the mass fraction of sodium alginate contained in the prepared pregel solution is 4%, and the mass fraction of polyacrylamide is 5%.
[0050] Embodiment 6:
[0051] A method for preparing a flexible fibrous aqueous zinc-iodine battery, the specific preparation steps are as follows:
[0052] (1) Preparation of pre-gel solution
[0053] 4% by mass of sodium alginate and 3% by mass of polyacrylamide were added into deionized water, and the mixture was stirred and dissolved to obtain a transparent solution.
[0054] (2) Preparation of fibrous zinc anode
[0055] Zinc wire (0.3 mm in diameter) was used as the fibrous zinc negative electrode.
[0056] (3) Preparation of fibrous iodine positive electrode
[0057] Activated carbon and solid iodine particles (mass ratio 1:1) were ground in a mortar to mix them thoroughly, and then transferred to a sealed reagent bottle and heated at 60°C for 12 hours. After cooling, iodine-loaded activated carbon, conductive carbon black (Super P), polytetrafluoroethylene binder, and sodium carboxymethyl cellulose were mixed in a mass ratio of 7:1:1.4:0.6 and deionized water was added to stir to form a uniform slurry. The above slurry was coated on the carbon fiber by impregnation, and the iodine-containing carbon fiber positive electrode was obtained after drying;
[0058] (4) Assembly of fibrous zinc-iodine batteries
[0059] The zinc wire was immersed in an aqueous solution of sodium alginate and polyacrylamide and coated with a layer of pregel solution. -1 ZnSO4 After soaking in the aqueous solution for 10 minutes, a layer of gel electrolyte is formed on the surface of the zinc wire.
[0060] The zinc anode coated with gel electrolyte was twisted with the iodine-loaded carbon fiber cathode, and then coated with a layer of pre-gel solution at a concentration of 0.5 mol·L -1 ZnSO 4 The electrodes were immersed in aqueous solution for 10 minutes to form a layer of gel electrolyte that wrapped around the electrodes, thereby obtaining a fiber-shaped zinc-iodine battery cell.
[0061] (5) Packaging
[0062] The battery cell prepared in the previous step is coated with silicone rubber and encapsulated to obtain a flexible fibrous zinc-iodine battery.
[0063] Example 7
[0064] A method for preparing a flexible fibrous aqueous zinc-iodine battery, the specific preparation steps are as follows:
[0065] (1) Preparation of pre-gel solution
[0066] 4% by mass of sodium alginate and 3% by mass of polyacrylamide were added into deionized water, and the mixture was stirred and dissolved to obtain a transparent solution.
[0067] (2) Preparation of fibrous zinc anode
[0068] Zinc wire (0.3 mm in diameter) was used as the fibrous zinc negative electrode.
[0069] (3) Preparation of fibrous iodine positive electrode
[0070] Activated carbon and solid iodine particles (mass ratio 1:1) were ground in a mortar to mix them thoroughly, and then transferred to a sealed reagent bottle and heated at 60°C for 12 hours. After cooling, iodine-loaded activated carbon, conductive carbon black (Super P), polytetrafluoroethylene binder, and sodium carboxymethyl cellulose were mixed in a mass ratio of 7:1:1.4:0.6 and deionized water was added to stir to form a uniform slurry. The above slurry was coated on the carbon fiber by impregnation, and the iodine-containing carbon fiber positive electrode was obtained after drying;
[0071] (4) Assembly of fibrous zinc-iodine batteries
[0072] The zinc wire was immersed in an aqueous solution of sodium alginate and polyacrylamide to coat a layer of pre-gel solution, and then -1 After being immersed in an aqueous solution of zinc trifluoromethanesulfonate for 10 minutes, a layer of gel electrolyte is formed on the surface of the zinc wire.
[0073] The zinc anode coated with gel electrolyte was twisted with the iodine-loaded carbon fiber cathode, and then coated with a layer of pre-gel solution at 0.5 mol·L -1 The electrodes were immersed in a zinc trifluoromethanesulfonate aqueous solution for 10 minutes to form a layer of gel electrolyte that wrapped around the electrodes, thereby obtaining a fibrous zinc-iodine battery cell.
[0074] (5) Packaging
[0075] The battery cell prepared in the previous step is coated with silicone rubber and encapsulated to obtain a flexible fibrous zinc-iodine battery.
[0076] Embodiment 8:
[0077] A method for preparing a flexible fibrous aqueous zinc-iodine battery, the specific preparation steps are as follows:
[0078] (1) Preparation of pre-gel solution
[0079] 4% by mass of sodium alginate and 3% by mass of polyacrylamide were added into deionized water, and the mixture was stirred and dissolved to obtain a transparent solution.
[0080] (2) Preparation of fibrous zinc negative electrode:
[0081] First, the carbon fiber bundles were cleaned with water and ethanol, and then immersed in concentrated nitric acid for 1 h to make the carbon fibers have a hydrophilic surface. Then, zinc was deposited on the carbon fiber surface by electrodeposition, and the deposition solution was 0.5 mol·L -1 Sodium citrate and 0.2 mol·L -1 Mixed aqueous solution of zinc sulfate, adjust the pH value of the deposition solution to 5-5.5 with dilute sulfuric acid. Use carbon fiber as working electrode, graphite rod as counter electrode, saturated calomel electrode as reference electrode, and electrodeposit at a constant voltage of -1.5V for 30min. Take out the carbon fiber and wash it with water to obtain the carbon fiber negative electrode for electrodepositing zinc.
[0082] (3) Preparation of fibrous iodine positive electrode
[0083] Activated carbon and solid iodine particles (mass ratio 1:1) were ground in a mortar to mix them thoroughly, and then transferred to a sealed reagent bottle and heated at 60°C for 12 hours. After cooling, iodine-loaded activated carbon, conductive carbon black (Super P), polytetrafluoroethylene binder, and sodium carboxymethyl cellulose were mixed in a mass ratio of 7:1:1.4:0.6 and deionized water was added to stir to form a uniform slurry. The above slurry was coated on the carbon fiber by impregnation, and the iodine-containing carbon fiber positive electrode was obtained after drying;
[0084] (4) Assembly of fibrous zinc-iodine batteries
[0085] The electro-deposited zinc carbon fiber was immersed in an aqueous solution of sodium alginate and polyacrylamide to coat a layer of pre-gel solution, and then-1 ZnSO 4 After soaking in the aqueous solution for 10 min, a layer of gel electrolyte is formed on the surface;
[0086] The zinc anode coated with gel electrolyte was twisted with the iodine-loaded carbon fiber cathode, and then coated with a layer of pre-gel solution at 0.5 mol·L -1 ZnSO 4 The electrodes were immersed in aqueous solution for 10 minutes to form a layer of gel electrolyte that wrapped around the electrodes, thereby obtaining a fiber-shaped zinc-iodine battery cell.
[0087] (5) Packaging
[0088] The battery cell prepared in the previous step is coated with silicone rubber and encapsulated to obtain a flexible fibrous zinc-iodine battery.
[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A flexible fiber-shaped aqueous zinc-iodine battery that is resistant to bending and has a long lifespan, characterized in that: include: A flexible fiber zinc negative electrode, a hydrogel electrolyte and a flexible fiber positive electrode, wherein the flexible fiber negative electrode is one of zinc wire, galvanized stainless steel wire, and carbon fiber with electroplated zinc, the hydrogel electrolyte is a double network hydrogel composed of sodium alginate and polyacrylamide, and the flexible fiber negative electrode is a carbon fiber coated with an iodine-containing positive electrode slurry.
2. The method for preparing a bending-resistant, long-life flexible fibrous aqueous zinc-iodine battery according to claim 1, characterized in that: The method comprises the following specific preparation steps: Step 1: immerse the flexible fiber zinc negative electrode in an aqueous solution of sodium alginate and polyacrylamide to coat a layer of pre-gel solution, and then immerse the fiber zinc negative electrode in a zinc salt aqueous solution to form a layer of gel electrolyte on the surface; Step 2: Mix iodine-loaded activated carbon, conductive carbon black, polytetrafluoroethylene binder, and sodium carboxymethyl cellulose, add deionized water and stir to form a uniform slurry, apply the slurry on carbon fiber by dipping, and obtain an iodine-containing carbon fiber positive electrode after drying; Step 3: The flexible fiber zinc negative electrode coated with gel electrolyte is twisted with the iodine-loaded iodine-containing carbon fiber positive electrode, and then coated with a layer of pre-gel solution of sodium alginate and polyacrylamide, and immersed in a zinc salt aqueous solution to form a layer of gel electrolyte to wrap the electrode, thereby obtaining a fiber-shaped zinc-iodine battery cell; Step 4: The battery cell prepared in the previous step is coated with silicone rubber to encapsulate a flexible fibrous zinc-iodine battery.
3. The method for preparing a bending-resistant, long-life flexible fibrous aqueous zinc-iodine battery according to claim 2, characterized in that: The mass fraction of sodium alginate in the pre-gel solution of the hydrogel electrolyte is 2% to 5%, and the mass fraction of polyacrylamide is 0.5% to 5%.
4. A method for preparing a bending-resistant, long-life flexible fibrous aqueous zinc-iodine battery according to any one of claims 2 to 3, characterized in that: The zinc salt is a mixture of one or more of zinc sulfate, zinc trifluoromethanesulfonate, zinc chloride, and zinc acetate, and the zinc salt concentration is 0.5 to 3.0 mol·L -1 The soaking time is 5min~6h.
5. The method for preparing a bending-resistant, long-life flexible fibrous aqueous zinc-iodine battery according to any one of claim 4, characterized in that: The iodine loading on the iodine-containing carbon fiber positive electrode is 0.2-2 mg cm -1 .
Citation Information
Patent Citations
Aqueous zinc ion battery electrolyte membrane and preparation and application method thereof
CN110085925A
Solid-state rechargeable zinc air / iodine hybrid battery based on polymer electrolyte
CN115842198A
Cited By
Hydrogel electrolyte modified by strong polar group as well as preparation method and application of hydrogel electrolyte
CN120637633A